EVALUASI EFEKTIVITAS SISTEM PENGENDALIAN INTERNAL PENERIMAAN DAN PENGELUARAN KAS PADA PT. SIARPLAN UTAMA KONSULTAN - Maria Florensia Pala Liru (2021)
This study aims to determine how the implementation and effectiveness of the internal control system of cash receipts and disbursements at PT. Main Consultant Plan, whether the internal control system that has been implemented has been running effectively or not. The theory used refers to Mulyadi's theory, and the method used in this research is qualitative with an ethnomethodological approach and uses an interpretive paradigm. Data collection techniques used are interviews, observation and documentation with key informants and supporters. The result of this research is PT. Siarplan Utama Consultants have implemented an effective internal control system for cash receipts and disbursements, but there are some practices that are not appropriate, namely the use of forms that are not printed serial numbers and there is no exchange of positions during the company's existence. PT. Overall, the Master Plan has implemented the effectiveness of an effective internal control system.